SISTEM ORGANISASI SOSIAL DAN KEMASYARAKATAN SUKU BADUY - Eti Susanti; Sapriya; Supriatna, Encep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Baduy community, located in Lebak Regency, Banten Province, Indonesia, represents an indigenous group that has preserved ancestral traditions amidst modernization. This article explores the social organization system of the Baduy community, including its hierarchical structure, customary norms, leadership roles, and interactions with the outside world. The social structure, led by the Puun as the spiritual leader and the Jaro as the administrative manager, is central to the community's continuity. Customary norms, known as